Racial/ethnic differences in job loss for women with breast cancer - Mujahid, Mahasin S. (Springer US, 2010)
INTRODUCTION: We examined race/ethnic differences in treatment-related job loss and the financial impact of treatment-related job loss, in a population-based sample of women diagnosed with breast cancer. METHODS: Three thousand two hundred fifty two women with non-metastatic breast cancer diagnosed (August 2005–February 2007) within the Los Angeles County and Detroit Metropolitan Surveillance Epidemiology and End Results registries, were identified and asked to complete a survey (mean time from diagnosis = 8.9 months). Latina and African American women were over-sampled (n = 2268, eligible response rate 72.1%). RESULTS: One thousand one hundred eleven women (69.6%) of working age (<65 years) were working for pay at time of diagnosis. Of these women, 10.4% (24.1% Latina, 10.1% African American, 6.9% White, p < 0.001) reported that they lost or quit their job since diagnosis due to breast cancer or its treatment (defined as job loss). Latina women were more likely to experience job loss compared to White women (OR = 2.0, p = 0.013)), independent of sociodemographic factors. There were no significant differences in job loss between African American and White women, independent of sociodemographic factors. Additional adjustments for clinical and treatment factors revealed a significant interaction between race/ethnicity and chemotherapy (p = 0.007). Among women who received chemotherapy, Latina women were more likely to lose their job compared to White women (OR = 3.2, p < 0.001), however, there were no significant differences between Latina and White women among those who did not receive chemotherapy. Women who lost their job were more likely to experience financial strain (e.g. difficulty paying bills 27% vs. 11%, p < 0.001). CONCLUSION: Job loss is a serious consequence of treatment for women with breast cancer. Clinicians and staff need to be aware of aspects of treatment course that place women at higher risk for job loss, especially ethnic minorities receiving chemotherapy.